In-situ examination of graphene and graphene oxide impact on the depuration of phenanthrene and fluoranthene adsorbed onto spinach (Spinacia oleracea L.) leaf surfaces. (June 2018) - Sun, Haifeng; Feng, Ruijie; Nan, Yanli; Chen, Zhang; Sang, Nan
Abstract: To further assess the human being's exposure to polycyclic aromatic hydrocarbons (PAHs) through the dietary pathway, understanding the partitioning of these chemicals co-existed with nanomaterials in edible vegetable systems deserves specific consideration. In this study, the fiber-optic fluorimetry was applied to in situ examine the effects of graphene (GNS) and graphene oxide (GO) nanosheets on the quantification and depuration of three-ringed phenanthrene (Phe) and four-ringed fluoranthene (Fla) adsorbed individually onto the living spinach ( Spinacia oleracea L.) surfaces. When the GNS and GO dosages separately increased to the maximum values: a respective red-shift of 4–5 nm and blue-shift of 2–3 nm occurred for the optimal detection emission wavelengths ( λ em ) of the two PAHs, indicating that individual GNS and GO resulted in different changes to the epicuticular wax (ECW) polarity; GNS-inducing fluorescence quenching for the PAHs was about two times greater than GO, owing to the stronger π-π interactions between PAH molecules and GNS relative to GO; the volatilization coefficients ( k C1 ) were reduced by 31.1% versus 26.7% for Phe, and 51.6% versus 34.4% for Fla, mainly via providing an additional adsorbent and promoting the accessibility of the leaf cuticle; respective photolysis coefficients ( k P2 ) of Phe and Fla decreased by 42.9% and 50.0% with GNS, primarily owing to the enhancement of the ECW light-adsorption capacity, but increased by 33.3% and 40.0% with GO due to its photocatalytic activities; overall, total depuration coefficients ( k T1, k T2 ) of the two PAHs decreased by 11.1–55.6%. These findings demonstrate that GNS and GO significantly alter the depuration behavior of PAHs in vegetable systems, potentially posing a threat to the safety of edible vegetables. Graphical abstract: Image 1 Highlights: Effects of GNS and GO on the clearance of Phe and Fla were examined in situ . GNS and GO had varied effects on the fluorescence spectra of adsorbed PAHs. The coexisting GNS and GO inhibited the volatilization of adsorbed PAHs. The presence of GNS inhibited the photolysis of PAHs, but GO promoted that. Abstract : GNS and GO inhibited the overall depuration of PAHs adsorbed onto living spinach leaf surfaces.